Unsur Intrinsik Puisi “Dendam” Karya Chairil Anwar - Garin Mahariz Setiawan; Jidan Maulana Yusup (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
reference put forward by I.A. Richards where he put forward an element, namely an intrinsic element which is used as the main component in writing a poem. These intrinsic elements consist of several elements, namely physical elements and mental elements. By using a qualitative method that focuses on a text as an object, by carrying out a library study approach where we look for data through journals/articles and books in developing a problem formulation (1) how are intrinsic elements implemented in poetry?, (2) Why are intrinsic elements called elements? builder in a poem?, (3) What are the results of the analysis carried out by students in analyzing the poem Dendam by Chairil Anwar?. with research objectives to (1) find out the implementation of intrinsic elements in livelihood poetry, (2) find out how intrinsic elements are said to be building blocks in a poem, (3) find out the results of the analysis of intrinsic elements in Chairil Anwar's revenge poem.